The correlations of interpersonal communication pharmacists with compliance medication in patientof diabetes mellitus type 2 - Meylinda Widyasari; Rina Herowati; Samuel Budi H (Universitas Aisyah Pringsewu, 2023)
Drug compliance is often associated with interpersonal relationships. Good interpersonal relationships depend on how interpersonal communication is established. This study aims to identify the relationship between interpersonal communication of pharmacists and drug compliance of Type 2 Diabetes Mellitus (DM) outpatients and identify the most dominant interpersonal and communication factors influencing drug compliance and its external factors. The samples of this study were patients who met the inclusion criteria. Data were obtained from questionnaires, observations, and medical records. The data were tested for validity and reliability using univariate analysis, bivariate analysis using chi-square, and multivariate analysis using multiple logistic regression. The results of the study showed characteristics that affect drug compliance are DM drugs used and the number of drugs received. The results of bivariate analysis p-value less than 0.05 mean there was a relationship between the interpersonal communication of pharmacists (openness, empathy, supportive behavior, positive behavior, and equality) and drug compliance of Type 2 DM outpatients at RSUD Jaraga Sasameh. The most dominant interpersonal communication factor was positive behavior with an exp (B) value of 16.013. External factors affecting were supporting facilities, and time. Abstrak: Kepatuhan minum obat seringkali dikaitkan dengan hubungan interpersonal. Hubungan interpersonal yang baik tergantung bagaimana sebuah komunikasi interpersonal dibangun. Penelitian ini bertujuan untuk mengetahui hubungan komunikasi interpersonal apoteker dengan kepatuhan minum obat pasien DM Tipe 2 rawat jalan, mengetahui faktor komunikasi interpersonal paling dominan dan faktor eksternal yang mempengaruhi kepatuhan minum obat. Sampel adalah pasien yang memenuhi kriteria inklusi. Data diperoleh dari pengisian kuesioner oleh pasien, observasi dan rekam medik. Kuesioner sebelum digunakan untuk pengambilan data di uji validitas dan reliabilitas. Data yang diperoleh dari kuesioner kemudian dianalisis univariat, bivariat menggunakan chi square dan multivariat menggunakan regresi logistik berganda. Hasil penelitian menujukkan karakteristik yang mempengaruhi kepatuhan minum obat yaitu obat DM yang digunakan dan jumlah item obat yang diterima. Hasil menganalisis bivariat angka p kurang dari 0,05 maknanya ada relasi diantara komunikasi interpersonal apoteker (keterbukaan, empati, tingkah laku suportif, tingkah laku positif serta kesetaraan) dengan ketaatan minum obat pasien DM Tipe 2 rawat jalan pada RSUD Jaraga Sasameh. Hasil analisis multivariat faktor komunikasi interpersonal paling dominan adalah perilaku positif dengan nilai exp (B) sebesar 16,013. Faktor eksternal yang mempengaruhi adalah sarana penunjang, dan waktu.